EFEKTIVITAS MODEL PEMBELAJARAN DIGITAL MIND MAPPING UNTUK MENINGKATKAN KREATIVITAS PESERTA DIDIK PADA ERA ABAD-21 (Studi Quasi Experiment dalam Pembelajaran PPKn di Kelas XI MIPA 1 SMAN 1 Majalengka) - fajar bagja gumilar winata, - (2021)
This study aims to empirically test the effectiveness of PPKN learning using digital mind mapping learning model to the creativity of learners. The sample of this study is students of class XI MIPA 1 SMAN 1 Majalengka as an experimental class. This study uses quantitative approach with quasi method of pretest-posttest design experiment, data collection is conducted with research instruments in the form of pretest-posttest questions in experimental classes and control classes, measurement instruments of student creativity and questionnaires that refer to indicators of student creativity. Data analysis using Normalized Gain statistical test with statistical test hypothesis testing. The results showed an increase in the category of creativity of learners in the results of pretest-posttest in experimental classes that use digital mind mapping learning models, there was an increase in the low category of creativity of learners in the results of pretest-posttest tests in the control class using mind mapping models, there were differences in creativity skills seen from N-Gain in pretest-posttest test results in experimental classes and control classes , Digital mind mapping learning model is effective to increase the creativity of learners in learning PPKn.